Frontispiece: A Visible–Near‐Infrared Light‐Responsive Host–Guest Pair with Nanomolar Affinity in Water. Issue 14 (7th March 2019) - Ferreira, Pedro; Ventura, Barbara; Barbieri, Andrea; Da Silva, José P.; Laia, César A. T.; Parola, A. Jorge; Basílio, Nuno
Abstract : A nanomolar affinity photoresponsive host–guest complex formed from cucurbit[8]uril and a diarylethene guest can be actuated with visible and near‐infrared light. (Frontispiece artwork provided by Gaia Barbieri.) For more information see the Communication by A. J. Parola, N. Basílio et al. onpage 3477 .